Demographic and epidemiologic evaluation of mushroompoisoning: a retrospective study in 4-year admissions of Razi Hospital (Qaemshahr, Mazandaran, Iran) - Iraj Goli Khatir; Seyed Mohammad Hosseininejad; Seyed Khosro Ghasempouri; Ailin Asadollahpoor; Siavash Moradi; Fatemeh Jahanian (Medicinski glasnik, 2019)
Aim: Wild mushroom intoxication is a public health problem, which causes a wide range of symptoms: from mild gastrointestinal symptoms to multiple organ failure and death. The present study aims to evaluate the epidemiology of mushroom intoxication in 4-year admissions of Razi Hospital, Qaemshahr, Mazandaran, Iran. Methods: Medical records of all identified cases of mushroom poisoning admitted during the period between 2015 and 2018 were extracted and patients' demographic data including age, sex, latency period, season of poisoning, clinical presentations, laboratory findings, prognosis, duration of hospitalization and therapeutic interventions were recorded. Results: A total of 65 mushroom poisoning cases were identified (mean age of 35.68 years), of which 32 (49.2%) were females. Latency of ? 6 hours was seen in 63 (96.4%) cases. The most prevalent season of intoxication was spring (60.7%). The most frequent symptoms were nausea and vomiting (86.5%) and abdominal pain (51.2%). No case required intensive care unit (ICU) care or mechanical ventilation. Mean hospital stay was 1.89 days without any mortality. Mean aspartate aminotransferase (AST) level was 21.89 (±9.55), but the disturbance of liver function tests (LFTs), coagulopathy, elevated level of bilirubin and/or platelet was not noted. In 93% of patients ranitidine, in 7% Penicillin G, and in 3.6% cefaclor and ceftriaxone was administrated. Conclusion: People and health care providers must be educated about mushroom poisoning. Prompt transfer of suspicious cases with history of wild mushroom ingestion to the emergency department is crucial since patients showing toxicity symptoms after 6 hours might have worse and mortal prognosis despite treatment.
Keywords: epidemiology; intoxication; poisoning; wild mushroom